Peran Pijat Oksitosin dalam Optimalisasi Produksi ASI: Laporan Asuhan Kebidanan Nifas Komprehensif di RSUD Dr. H. Jusuf SK Tarakan - Thisna Damayanty; Vistra Veftisia (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Midwifery care is a crucial part of maternal and child health care, especially for mothers who have just given birth. The postpartum period extends from a few hours after the placenta is delivered to 6 weeks or 42 days. Insufficient breast milk production can lead to insufficient supply to the baby. Decreased breast milk production in the first few days after delivery can be caused by insufficient stimulation of the hormones prolactin and oxytocin. Therefore, midwifery care for postpartum mothers, including oxytocin massage, is essential. The method used is descriptive. The report is a case study, involving a postpartum mother at Dr. H. Jusuf SK Tarakan Regional Hospital. Results obtained during comprehensive care revealed the patient complained of insufficient breast milk production. Midwives provide implementation of midwifery care by administering oxytocin massage. The conclusion is that comprehensive midwifery care has been provided starting from pregnancy, childbirth, postpartum, neonates, newborns so that mothers avoid complications and are able to provide smooth breastfeeding to their babies after being given oxytocin massage.   Abstrak Masalah utama yang dihadapi ibu nifas adalah penurunan/ketidakcukupan produksi ASI akibat kurangnya stimulasi hormon prolaktin dan oksitosin. Oleh karena itu, diperlukan intervensi non-farmakologis, seperti Pijat Oksitosin. Tujuan studi kasus ini adalah menganalisis efektivitas penerapan Pijat Oksitosin dalam upaya peningkatan produksi ASI pada ibu nifas. Metode yang digunakan adalah metode deskriptif. Jenis laporan yang digunakan adalah studi kasus (Case Study) yaitu dengan cara mengambil kasus ibu nifas di RSUD Dr. H Jusuf SK Tarakan. Intervensi Pijat Oksitosin diberikan selama tiga hari dua kali sehari dengan durasi 15 menit.  Hasil menunjukkan bahwa setelah intervensi Pijat Oksitosin, terjadi peningkatan signifikan pada produksi ASI ibu. Kesimpulan: Pijat Oksitosin terbukti efektif.